Pengaruh Kompensasi dan Lingkungan Kerja terhadap Kinerja Karyawan Melalui Motivasi Kerja sebagai Variabel Intervening pada PT. Agro Masang Perkasa Plantation Kabupaten Agam - Hendri, Venni Rahmatia; Hilda Mary; Andry Novrianto (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
This study aims to examine the influence of compensation and work environment on employee performance through work motivation. Using primary data, a questionnaire was distributed to 128 employees at PT. Agro Masang Perkasa Plantation in Agam Regency. This study used structural equation modeling (SEM) analysis using Partial Least Squares (PLS). The results show that there is compensation that has a positive and significant effect on work motivation with a P-value of 0.024 <0.05, there is a work environment that has a positive and significant effect on work motivation with a P-value of 0.000 <0.05, there is compensation that has a positive and insignificant effect on employee performance with a P-value of 0.145>0.05, there is a work environment that has a negative and insignificant effect on performance with a P-value of 0.794>0.05, there is work motivation that has a positive and significant effect on employee performance with a P-value of 0.000 <0.05, there is compensation through work motivation that has a positive and significant effect on employee performance with a P-value of 0.041 <0.05 and there is a work environment through work motivation that has a positive and significant effect on employee performance with a P-value of 0.009 <0.05.